Keep Healthy With Zumba Exercise - Sontina Saragih; M. Kustiriani Frutasari; Ria Angelina Marbun; Lidya Maryani; Kalvin Ginting; Ziska Herawaty; Yuana Dwi Agustin; Mark Ochoa (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The increasing prevalence of non-communicable diseases such as diabetes, hypertension, cardiovascular disorders, and respiratory illnesses underscores the need for comprehensive, preventive community health initiatives. Zumba, an energetic and enjoyable form of physical activity, provides an innovative approach to exercise that improves physical, mental, and social well-being. This exercise not only helps burn calories and enhance cardiovascular fitness but also stimulates endorphin release, contributing to mood improvement and stress reduction. Conducted as a group-based activity, Zumba fosters social and family interaction, strengthening emotional support and community togetherness. By combining the benefits of exercise and social engagement in a lively and inclusive environment, Zumba serves as an effective health promotion strategy to promote healthy lifestyles and enhance quality of life at the community level.